Fluoride Ions Release Study Of Different GIF Materials (Mustansiria Dental Journal, 2018)
The purpose of this in vitro study was to compare & measure the release of fluoride ions from set tested materials, CGI (Pro-med), MGI (Ketac molar), and LCGI (Vitremer).The tested materials were made as molds with certain dimensions and each mold was placed in vial containing 100 ml. of DDW. Every 24 hrs, 5 ml. of the solution was transferred into smaller tubes to measure the fluoride release using spectrophotometer. This procedure was repeated every 24 hrs. for 14 days.The results revealed that the CGI (conventional glass ionomer) had higher release over other materials, then the MGI (modified glass ionomer) material, and finally the LCGI (light cure glass ionomer) with significant differences between them at P< 0.05.The MGI material had higher fluoride ions release concentrations over the LCGI. However, the CGI had higher fluoride ions release concentrations over other materials.